Impact of dyslipidemia on the cumulative pregnancy outcomes after first ovarian stimulation - Jiang, Xue; Lu, Xinle; Cai, Mingshu; Liu, Yu; Guo, Yihong (Frontiers in Endocrinology, 2022)
Objectives: To investigate the cumulative live birth rate (CLBR) according to lipid metabolism in patients with or without polycystic ovarian syndrome (PCOS) undergoing their first complete in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles. Patients: A total of 1,470 patients with PCOS and 3,232 patients without PCOS who underwent their first complete IVF/ICSI cycles from January 2016 to June 2018 were included. During a minimum of 2 years of follow-up, they had achieved at least one live birth or used all available embryos.The cumulative pregnancy outcomes were compared based on the patients’ blood lipid parameters in the two populations, including triglycerides (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C). Patients with an abnormal level of one or more of these four indicators were considered the dyslipidemia group. Patients whose four indicators were normal were considered the control group. Results: Among 1,470 patients with PCOS, the cumulative pregnancy outcomes were comparable in the dyslipidemia group and control group. Logistic regression analysis showed that the TC levels were significantly negatively associated with the cumulative live birth rate (CLBR) after adjustment for confounding factors such as age and BMI (aOR 0.81, 95% CI 0.66-0.98, P<0.05). Among the 3,232 patients without PCOS, there was no significant difference in the cumulative pregnancy outcomes between the dyslipidemia group and the control group. No significant correlations were found in other logistic regression analyses. Conclusions: TC negatively impacts the CLBR after first ovarian stimulation in PCOS patients. PCOS patients with dyslipidemia caused by elevated TC may have a poor CLBR.